2020
DOI: 10.3390/jcm9092813
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Robot-Assisted Gait Training in Patients with Burn Injury on Lower Extremity: A Single-Blind, Randomized Controlled Trial

Abstract: This study investigated the effects of robot-assisted gait training (RAGT) on gait function in burn patients. Briefly, 40 burn patients were randomly divided into an RAGT group or a conventional training (CON) group. SUBAR® (Cretem, Korea) is a wearable robot with a footplate that simulates normal gait cycles. The RAGT group underwent 30 min of robot-assisted training using SUBAR® with 30 min of conventional physiotherapy once a day, 5 days a week for 12 weeks. Patients in the CON group received 30 min of over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…From the perspective of the scientist, this gathering had absence of information in regards to security precautionary measures that expansion danger of consume damage. This finding compatible with (Joo et al, 2020), who demonstrated that, around half of consumed patients had essential and auxiliary instruction. Then again, (Elsherbiny et al, 2011) expressed that, the dominant part of consumed subjects were ignorant; this outcome was conversely with the consequence of present investigation.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…From the perspective of the scientist, this gathering had absence of information in regards to security precautionary measures that expansion danger of consume damage. This finding compatible with (Joo et al, 2020), who demonstrated that, around half of consumed patients had essential and auxiliary instruction. Then again, (Elsherbiny et al, 2011) expressed that, the dominant part of consumed subjects were ignorant; this outcome was conversely with the consequence of present investigation.…”
Section: Discussionsupporting
confidence: 89%
“…As respects to conjugal status, the most astounding rate was married, this result was in harmonious with (Elsherbiny, Salem, El-Sabbagh, Elhadidy, & Eldeen, 2011); (Joo et al, 2020), who found that, the lion's share of consumed patients were hitched. Then again, Edwards, (2013) detailed that, the greater part of single grown-up most normally influenced with consume damage.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Robotic therapy for musculoskeletal disorders is performed to allow intensive and repetitive training to increase the range of motion (ROM) and improve motor function [1]. While the clinical effectiveness of exoskeleton robot-assisted rehabilitation has been confirmed in burn patients [2][3][4], robotic therapy cannot be performed in patients who complain of severe pain during treatment. Therefore, there is a need for research on treatment methods that can reduce pain during robotic therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The primary goals of burn rehabilitation medicine are preventing the formation of burn scar contracture, improving the limited range of motion (ROM) of joints and limiting functional restrictions [ 1 ]. In particular, scar contracture of the lower extremities can lead to pain during walking and limited ROM of the hip, knee and ankle joints, which can result in gait disturbance [ 2 , 3 ]. Appropriate and sufficient rehabilitation therapy following burn injury can decrease hypertrophic scar formation and delay the progression of scar contracture in burn survivors [ 1 , 4 ].…”
Section: Introductionmentioning
confidence: 99%